Development of License Plate Recogniion System for Malaysian Vehicles - D. Saleh, Marwan (2009)
This research attempts to contribute to the current improvements of LPR based on some image processing techniques, in order to produce an efficient LPR system for Malaysian vehicles, and extending that system to be used in other countries, especially those using Latin characters. On the other hand, the proposed system capable of identifying vehicles in concise manner even under complex background, or under various illumination and climate circumstances, with taking into account the accuracy and the fast processing at the development.